Acute effect of outflow tract premature ventricular complex ablation on QT dispersion, Tp-e interval and Tp-e/QT ratio - KEPEZ, ALPER (TAYLOR & FRANCIS LTD, 2021)
Background: There is limited data regarding the effect of idiopathic premature ventricular complexes (PVC) on myocardial repolarisation. Most of PVC's originate from right and left ventricular outflow tracts (RVOT and LVOT). Aim: The aim of this study is to evaluate the acute effect of outflow tract PVC ablation on electrocardiographic repolarisation markers. Methods: A total of 180 patients (49.2 +/- 13.6 years, 74 male) without any exclusion criteria who had undergone outflow tract PVC ablation between 1 January 2015 and 1 November 2018 constituted our study population. Electrocardiographic recordings that had been obtained before and after ablation procedure on the same day were retrospectively evaluated for the QTc dispersion, Tp-e interval, Tp-e/QT ratio and Tp-e/QTc ratio. Significance of difference between pre- and postablation values was tested. Results: There was no significant difference regarding QTc dispersion between pre- and post-ablation state (36.5 +/- 20.9 vs. 35.3 +/- 16.4 ms, p: NS). However, Tp-e and Tp-e/QT values in all lateral precordial derivations were observed to decrease significantly after PVC ablation (in the respective order on derivation V5: 104.0 +/- 21.6 ms vs. 91.1 +/- 14.8 ms, pvs. 0.23 +/- 0.04, p<.001). Conclusions: Based on these observations, it may be suggested that frequent outflow tract PVC's increase transmural dispersion of repolarisation and this effect is attenuated by catheter ablation in the acute phase. Results of further prospective studies are required for evaluation of the long term effects of PVC ablation on myocardial repolarisation.
Keywords: Outflow tract premature ventricular complex; catheter ablation; myocardial repolarisation; QT dispersion; Tp-e interval; Tp-e; QT ratio; MARKERS